Effect of Lactic Acid Bacteria Addition on the Microbiological Safety of Pasta-Filata Types of Cheeses - Medved’ová, Alžbeta; Koňuchová, Martina; Kvočiková, Karolína; Hatalová, Ivana; Valík, L’ubomír (Frontiers in Microbiology, 2020)
In this work, the effects of different combinations of lactic acid bacteria (LAB) on the growth of coagulase-positive staphylococci (CPS) and Escherichia coli were evaluated during ripening of 23 curd cheeses, and their subsequent behavior during the manufacture and storage of pasta-filata cheeses was characterized. Three groups of cheeses were prepared in total: first, control cheeses from raw milk without LAB addition; further raw milk cheeses with LAB added; and finally, pasteurized milk cheeses with LAB, CPS and E. coli intentional inoculation. Based on the results, counts of CPS increased over 24 hours in control curd cheese by 1.76 ±0.56 log CFU/g. On the other hand, in raw milk cheeses with the addition of starter culture, the increase in CPS counts was 0.76 ±0.87 log CFU/g was noticed. Counts of E. coli increased during the first 24 h of curd manufacture by 3.56 ±0.41 log CFU/g in cheeses without LAB addition. Addition of the cultures to raw milk led to the inhibition of E. coli multiplication, resulting in an increase in E. coli counts of only 1.40 ±1.07 log CFU/g. After steaming at 63.6 ±1.9 °C for 7.2 ±2.1 min (temperature of heated acidified curd was 54.9 ±1.7 °C), CPS decreased by 0.58 ±1.12 log CFU/g, and E. coli decreased by 1.23 ±0.97 log CFU/g in all cheeses, regardless of LAB addition. Finally, during storage of cheeses at 6 ±0.5 °C for 28 days, the levels of E. coli in control cheeses and in raw milk LAB-enriched cheeses reached levels of 2.07 ±2.28 log CFU/g and 1.20 ±0.85 log CFU/g, respectively. Moreover, the counts of CPS at the end of storage met the criteria of EU Regulation No. 1441/2007 (less than 4 log CFU/g) in all manufactured cheeses with added LAB culture, while in the control raw milk cheeses, a level of 3.80 ±1.22 log CFU/g was observed. Regarding the culture used, the best microbiological inhibitory effect in 28-day-old cheeses was reached by the combination of Fresco culture with Lacticaseibacillus rhamnosus GG, and the best sensory properties were judged to be those for cheeses manufactured with Culture A.